GSK-3𝜷: A Bifunctional Role in Cell Death Pathways - Keith M. Jacobs; Sandeep R. Bhave; Daniel J. Ferraro; Jerry J. Jaboin; Dennis E. Hallahan; Dinesh Thotala (International Journal of Cell Biology)
Although glycogen synthase kinase-3 beta (GSK-3β) was originally named for its ability to phosphorylate glycogen synthase and regulate glucose metabolism, this multifunctional kinase is presently known to be a key regulator of a wide range of cellular functions. GSK-3β is involved in modulating a variety of functions including cell signaling, growth metabolism, and various transcription factors that determine the survival or death of the organism. Secondary to the role of GSK-3β in various diseases including Alzheimer’s disease, inflammation, diabetes, and cancer, small molecule inhibitors of GSK-3β are gaining significant attention. This paper is primarily focused on addressing the bifunctional or conflicting roles of GSK-3β in both the promotion of cell survival and of apoptosis. GSK-3β has emerged as an important molecular target for drug development.